The effect of luting techniques on the push-out bond strength of fiber posts - André Luis Faria e Silva; André Figueiredo Reis; Luis Roberto Marcondes Martins (Universidade Estadual de Campinas, 2015)
Aim: This study aimed to evaluate the effect of using a chemical co-initiator and/or an additional coat of a hydrophobic resin on the bond strength of fiber posts luted with a dual-cured resin cement. In addition, the use of the resin cement only was also evaluated. Methods: Fiber posts were luted with dual-cured resin cement (Enforce) and using one of five adhesive procedures: G1 - Prime&Bond 2.1 (PB), G2 - PB + Self-cure activator (SC), G3 - PB + bonding agent of Scotchbond Multi-Purpose (SMP), G4 - PB + SC + SMP and G5 - no adhesive. The root samples were sectioned transversally into three slabs (coronal, middle and apical third) that were submitted to push-out testing. Data were submitted to split-plot ANOVA and Tukey's test (α = 0.05). Results: When the adhesives were used, the hydrophobic resin application (G3 and G4) increased fiber post retention in comparison to G2 only in the coronal third. For the other thirds, there was no difference between the adhesive methods. G5 presented the lowest values in the coronal and middle thirds, but it was similar to all other groups in the apical third. Conclusion: post retention seemed not to benefit from the adhesive application in the apical region.